Analisis Kritik Penonton terhadap Film Adaptasi A Business Proposal Versi Indonesia : Perspektif Media Sosial - Rodiyatul Adawiyah; Siti Mustika Yanti; Muhammad Naufal Fadillah; Revy Kurnia (Pusat Riset dan Inovasi Nasional, 2024)
In today's digital era, social media has become an important space for the public to express their opinions, including assessing film adaptations. This study examines audience criticism of the Indonesian version of the film adaptation of A Business Proposal that has spread on social media. Audience criticism focuses heavily on inconsistencies with the original version, acting quality, and technical aspects such as cinematography and directing. Factors that have influenced this criticism include audience perceptions of the original work, expectations of characters and stories, and the influence of discussions that have developed virally on social media. Massive criticism has an impact on audience interest, promotional strategies, and becomes evaluation material for filmmakers in developing better adaptations in the future. Social media is not only a channel of expression, but also a significant tool in shaping the success or failure of a film adaptation.